Model Sinergistas Lembaga Pegadaian Syariah dan Perguruan Tinggi Dalam Membentuk SDM Unggul Berbasis Syariah - Muhamad Iqbal; Muhamad Rahman Bayumi; Faisal Muttaqin; Muhamad Junestrada Diem (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
Sharia Pawnshop has transformed into one of the strengths of Islamic financial institutions whose existence is quite taken into account. The characteristics of sharia pawns that are solutive for the lower middle class are a strong factor in its progress from year to year. In line with that, the existence of Islamic economics and finance-based study programs in all PTKIN and even most PTN, brings new hope of producing superior sharia-based human resources. A hope that is just waiting for the momentum to make Indonesia a country of Islamic Economic Civilization in the world. Various efforts have been made to produce excellent students who will compete in the world of work, especially in Islamic financial institutions. However, the problem is that there is no relevance between the world of work and the basic knowledge of Islamic economics and finance that is owned, which is an irony and injures the spirit of printing sharia-based superior human resources. Many alumni work in conventional financial institutions, on the other hand, Islamic financial institutions lack sharia-based human resources. This study aims to describe the concept of human resource development in universities that are integrated with Islamic financial institutions, especially Sharia Pawnshop. There are three concrete steps that can be implemented through the integration-interconnection approach, namely the development of thematic courses, strengthening the role of laboratories, and optimizing field work practices for students. By providing an overview and analysis of the strengthening, it is hoped that it can contribute to the formation of superior sharia-based human resources.